Study on Some Body Organ Systems of the Wild African Senegal Parrot (Poicephalus senegalus versteri) - Wanmi, N.; Mohammed, A.; Nev, T. (Pakistan Journal of Nutrition, 2015)
Parrot population in Africa is declining and the need for conservation actions to address threats is increasingly recognized. The situation is worst in Nigeria and if care is not taken, this species of bird will soon go into instinct. The essence of this study was to obtain a data base of some body organs of the wild Senegal parrot which are scarce. Documentation on this species of bird is rare despite they are being hunted for because of its demand as ornamental bird. The mean weights (whole body, gastrointestinal tract (GIT)+content and GIT empty) were observed to be 120.50±5.42, 18.01±4.80 and 13.54±5.51 g, respectively. The liver had mean weight of 4.18±1.82 while the tongue, lower respiratory system (LRS), heart and kidney were observed to be, 2.76±2.14 g, 5.83±1.65, 1.81±0.65 and 0.41±0.05 g. The mean length (whole body+tail) were observed to be 9.85±1.20 cm. The mean lengths (GIT, liver tongue and LRS) were 82.62±2.36, 4.33±1.82, 2.04±0.99 and 12.69±2.10 cm with GIT and LRS accounting for 76.93 and 19.97%. The syrinx is very large suggesting sound production is pronounced and the large intestine is void of cecum.